Antiviral activity of porcine interferon omega 7 against foot‐and‐mouth disease virus in vitro - Li, Shi‐Fang; Zhao, Fu‐Rong; Gong, Mei‐Jiao; Shao, Jun‐Jun; Xie, Yin‐Li; Chang, Hui‐Yun; Zhang, Yong‐Guang (Journal of medical virology, 2019)
Foot‐and‐mouth disease (FMD) is a disease of worldwide economic importance, and vaccines play an important role in preventing FMDV outbreaks. However, new control strategies are still needed since FMDV outbreaks still occur in some disease‐free countries. Currently, interferon (IFN)‐based strategies have been demonstrated to be an efficient biotherapeutic option against FMDV; however, interferon omega (IFN‐ω) has not yet been assessed in this capacity. Thus, this study evaluated the antiviral activity of porcine IFN omega 7 (PoIFN‐ω7) against FMDV. After the PoIFN‐ω7 was expressed and purified, cell proliferation assays and quantitative real‐time reverse transciption‐polymerase chain reaction were used to evaluate the effective anti‐cytopathic concentration of PoIFN‐ω7 and its effectiveness pre‐ and post‐infection with FMDV in swine kidney cells (IBRS‐2). Results showed the rHis‐PoIFN‐ω7 fusion protein was considerably expressed using Escherichia coli BL21 (DE3) strain, and the recombinant protein exhibited significant in vitro protection against FMDV, including two strains belonging to type O and A FMDV, respectively. In addition, PoIFN‐ω7 upregulated the transcription of Mx1, ISG15, OAS1, and PKR genes. These findings indicated that IFN‐ω has the potential for serving as a useful therapeutic agent to prevent FMDV or other viral outbreaks in pigs. 1.PoIFN‐ω7 exerted effective antiviral activity against FMDV pre‐ and post‐infection in vitro. 2.PoIFN‐ω7 induced the transcription of IFN‐stimulated genes, including Mx1, ISG15, OAS1, and PKR genes.